Prática social de ressignificação da educação escolar indígena: compreendendo os processos educativos do cotidiano Terena do município de Aquidauana MS - Novais, Sandra Nara da Silva (Universidade Federal de São Carlos, 2013)
The research is part of the Research Line Social Practices and Educational Processes of the Program of Post Graduation in Education of the Federal University of São Carlos PPGE/UFSCar and aims to identify and describe social practices and educational processes experienced in the everyday of the Terena village of the indigenous Land Taunay/Ipegue in the city of Aquidauana Mato Grosso do Sul, which enable the understanding of how the practices present in the culture Terena may, or may not, dialogue with the indigenous school education. To achieve the proposed objective we established the following research questions: What practices present in the Terena culture form the basis of their everyday education? How these educational processes may, or may not, dialogue with the the education offered in the existing schools in the villages? What do the Terena consider important to be taught in school? How the Terena indigenous school has historically constituted itself in space time of dialogue between the different knowledges of the subjects involved in this educational reality? To compose the theoretical referential of the research we used of contributions developed by central authors of the Research Line, among them Enrique Dussel, Ernani Fiori and Paulo Freire where we locate ourselves drawing on experiences and existences in Latin America. This is an ethnographic research as proposed by André (1995) and Geertz (1989), which is based on the thick description of the social practices and the educational processes experienced in everyday life of the Terena villages of of the Indigenous Land Taunay/Ipegue. The methodological procedures used consist in the analysis of the records of the Journal Field of moments lived with the Terena of the studied villages; the interview is conducted by the circle of conversations (the circle of Tereré and the moments around the fire); of the consultation of the registration of parent-teacher meetings and other meetings in the villages in the period from 2000 to 2010, and photographs that record the daily life of the villages surveyed. The knowledge fruit of the research seeks to meet what is proposed by the research line Social Practices and Educational Processes PPGE/UFSCar which aims to provide the formation of researchers whose work will allow interventions in educational processes located in Latin America. Starting from what was lived we seek to raise a series of questions, inquiries and reflections which could contribute to closer the dialogue between the educational processes of the Terena indigenous culture, with what proposes the education offered in the existing schools in the villages of Terena Indian Land Taunay/Ipegue of the city of Aquidauana MS in the context of Brazilian cultural diversity.
Keywords: Educação; Práticas sociais e processos educativos; Vivência; Cotidiano; Índios Terena - cultura; Educação escolar indígena; Educational processes; Social practices; Experience and daily life; Terena culture; Formal education; CIENCIAS HUMANAS::EDUCACAO